Governance, Consumers and Citizens
X, 286 p.
Keywords: This is the first book to focus on governance and cultures of consumption, expanding the debate and raising new conceptions and policy agendas. It questions the changing place of the consumer as citizen in recent trends in governance, the tensions between competing ideas and practices of consumerism, and the active role of consumers in governance.